Development of Voluntary Assisted Dying Training in Victoria, Australia: A Model for Consideration. Issue 3 (July 2021) - White, Ben P.; Willmott, Lindy; Close, Eliana; Hewitt, Jayne; Meehan, Rebecca; Greaves, Laura Ley; Parker, Malcolm H.; Yates, Patsy
Background: Voluntary assisted dying was legalized in Victoria, Australia in June 2019, and was the first jurisdiction internationally to legislatively mandate training for doctors conducting eligibility assessments of patients. Mandatory training was designed as a safeguard to ensure compliance within the system, so that only eligible patients would gain access to voluntary assisted dying. Objective: This article outlines the development of training mandated for doctors prior to undertaking eligibility assessments for voluntary assisted dying. The training addressed required legal knowledge, including doctors' roles, duties and legal protections, and also provided instruction on relevant clinical skills. Design: Training design was based on 2 main principles: to comprehensively impart the legal duties imposed by the legislation; and to be readily accessible for busy doctors. The law was first mapped into a curriculum, and circulated to medical colleges, societies and professional organizations as well as international experts for feedback. The training was converted into an online e-learning format and tested at a focus group of doctors. Results: The training comprises 9 modules including an assessment module. While the predominant focus of the modules is on law, they also contain some clinical components and links to further resources. Modules also contain videos, case studies and interactive exercises. The assessment consists of 30 questions, selected randomly from a question bank, with a pass mark of 90%. Conclusion: The Victorian legislatively-mandated voluntary assisted dying training provides standardized baseline knowledge to enhance the quality and consistency of decision-making by doctors. While further evaluation of this training is needed, it may provide a model for other jurisdictions considering making voluntary assisted dying lawful.